2020
DOI: 10.1016/j.omto.2020.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of CD28- or 4-1BB-Based CD19 CAR-T Cells in B Cell Acute Lymphoblastic Leukemia

Abstract: CD19-directed chimeric antigen receptor-T (CAR-T) cells with a 4-1BB or CD28 co-stimulatory domain have shown impressive antitumor activity against relapsed or refractory B cell acute lymphoblastic leukemia (r/r B-ALL). However, a parallel comparison of their performances in r/r B-ALL therapy has not been sufficiently reported. Here, we manufactured 4-1BB- and CD28-based CD19 CAR-T cells using the same process technology and evaluated their efficacy and safety in r/r B-ALL therapy based on pre-clinical and exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
71
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 36 publications
(69 reference statements)
5
71
0
Order By: Relevance
“…The type of costimulatory ligand in CAR can greatly impact CAR T cell function and phenotype. For example, differences in phenotype between 28z and BBz have been demonstrated in animal models, which show that the 4-1BB signaling domain enhanced CAR T-cell memory development and persistence, and promoted oxidative phosphorylation and mitochondrial biogenesis, while the CD28 signaling domain pushed towards an effector phenotype and glycolysis [ 214 , 215 ]. Selecting the correct co-stimulatory domain, or combining multiple co-stimulatory domains, may therefore improve CAR T cell function.…”
Section: Possible Solutionsmentioning
confidence: 99%
“…The type of costimulatory ligand in CAR can greatly impact CAR T cell function and phenotype. For example, differences in phenotype between 28z and BBz have been demonstrated in animal models, which show that the 4-1BB signaling domain enhanced CAR T-cell memory development and persistence, and promoted oxidative phosphorylation and mitochondrial biogenesis, while the CD28 signaling domain pushed towards an effector phenotype and glycolysis [ 214 , 215 ]. Selecting the correct co-stimulatory domain, or combining multiple co-stimulatory domains, may therefore improve CAR T cell function.…”
Section: Possible Solutionsmentioning
confidence: 99%
“…On this issue, inconsistent results have been observed across the literature. Reports showed that T cells could persist for a relatively long time after T cells infusion (45)(46)(47). On the contrary, Li et al demonstrated that CAR-T cells could exist only for 5 to 7 days after CAR-T cells transfusion (48).…”
Section: Discussionmentioning
confidence: 99%
“…On this issue, inconsistent results have been observed across the literature. Reports showed that T cells could persist for a relatively long time after T cells infusion ( 45 47 ). On the contrary, Li et al.…”
Section: Discussionmentioning
confidence: 99%
“…Except for scFv clone selection, CAR structure considerations, especially costimulation region design, also affect CAR‐T cell response. Several preclinical studies and a few clinical trial results suggest that CAR‐T cells incorporating the 4‐1BB costimulatory domain may have better persistence compared with those involving the CD28 costimulatory domain (Kawalekar et al, 2016; Long et al, 2015; Milone et al, 2009; Philipson et al, 2020; Ying et al, 2019; Zhao et al, 2020). In this case, we performed a detailed comparison of Clone 78‐BBz CAR and FMC63‐BBz CAR from different aspects, which suggested that Clone 78‐BBz CAR‐T cells possess a function comparable with that of FMC63‐BBz CAR‐T cells in vitro or in murine models.…”
Section: Discussionmentioning
confidence: 99%